Natural adaptation and human selection of northeast African sheep genomes - Ahbara, A.M.; Musa, Hassan H.; Robert, C.; Abeba, A.; Al-Jumaili, A.S.; Kebede, Adebabay; Latairish, S.; Agoub, M.O.; Clark, E.; Hanotte, Olivier H.; Mwacharo, Joram M. (Elsevier, 2022)
African sheep manifest diverse but distinct physio-anatomical traits, which are the outcomes of natural- and human-driven selection. Here, we generated 34.8 million variants from 150 indigenous northeast African sheep genomes sequenced at an average depth of ∼54× for 130 samples (Ethiopia, Libya) and ∼20× for 20 samples (Sudan). These represented sheep from diverse environments, tail morphology and post-Neolithic introductions to Africa. Phylogenetic and model-based admixture analysis provided evidence of four genetic groups corresponding to altitudinal geographic origins, tail morphotypes and possible historical introduction and dispersal of the species into and across the continent. Running admixture at higher levels of K (6 ≤ K ≤ 25), revealed cryptic levels of genome intermixing as well as distinct genetic backgrounds in some populations. Comparative genomic analysis identified targets of selection that spanned conserved haplotype structures overlapping clusters of genes and gene families. These were related to hypoxia responses, ear morphology, caudal vertebrae and tail skeleton length, and tail fat-depot structures. Our findings provide novel insights underpinning morphological variation and response to human-driven selection and environmental adaptation in African indigenous sheep.